2020
DOI: 10.1088/1361-6641/abaa2a
|View full text |Cite
|
Sign up to set email alerts
|

Silicon nitride engineering: role of hydrogen-bonding in Ge quantum dot formation

Abstract: We report the lowering of the formation temperature of spherical-shaped Ge quantum dots (QDs) to 850 • C from our previously-reported 900 • C. This large reduction in QD formation temperature was achieved via the use of a hydrogenated, plasma-enhanced chemical-vapor deposited (PECVD) silicon nitride (SiN). The exquisite interplay between H, Ge, Si and O interstitials, controlling QD formation during the thermal oxidation of poly-SiGe layers deposited over PECVD-Si x N y : H, is further explored in order to und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…We have also experimentally observed a large increase in the local thickness of this conformal SiO 2 interlayer when the nature of the proximal Si 3 N 4 layer changes from a low-pressure chemical-vapor deposited (LPCVD)-Si 3 N 4 layer to plasma-enhanced chemical-vapor deposited (PECVD)-Si x N y : H layer [33]. This is because the significantly higher temperature (780 °C) deposition for LPCVD-Si 3 N 4 layers results in a much denser Si 3 N 4 film with lower hydrogen incorporation as compared to the PECVD-Si x N y : H layers which are nominally deposited at 300 • C and contain a higher concentration of Si-H and N-H bonds [34].…”
Section: Ge-qds-mediated Si 3 N 4 Oxidationmentioning
confidence: 81%
“…We have also experimentally observed a large increase in the local thickness of this conformal SiO 2 interlayer when the nature of the proximal Si 3 N 4 layer changes from a low-pressure chemical-vapor deposited (LPCVD)-Si 3 N 4 layer to plasma-enhanced chemical-vapor deposited (PECVD)-Si x N y : H layer [33]. This is because the significantly higher temperature (780 °C) deposition for LPCVD-Si 3 N 4 layers results in a much denser Si 3 N 4 film with lower hydrogen incorporation as compared to the PECVD-Si x N y : H layers which are nominally deposited at 300 • C and contain a higher concentration of Si-H and N-H bonds [34].…”
Section: Ge-qds-mediated Si 3 N 4 Oxidationmentioning
confidence: 81%
“…Measured Grüneisen parameters from temperature-dependent Raman frequencies suggest significant anharmonicity for small Ge QDs with possible distortions of the diamond cubic lattice, which have been confirmed by their lattice spacings through the transmission electron diffraction patterns. We have also observed that quantum phonon confinement effect sets in when the Ge QD size is smaller than 40 nm [ 47 , 48 , 49 ]. Therefore, the valley degeneracy in our Ge QDs could be split by tailoring the local environmental materials of SiO 2 or Si 3 N 4 in combination with adjusting the QD sizes by design.…”
Section: Discussionmentioning
confidence: 99%
“…The derived classification of crystal planes from the XRD spectra and the corresponding diffraction spots identified within the SAED are in good agreement. This densification of Si 3 N 4 also leads to the reduction in the concentration of hydrogen induced traps and thereby a significant improvement in the trap-assisted tunneling or hopping [ 49 , 52 ]. Low interface trap density (Dit) of ~2–3 × 10 11 cm 2 eV −1 was measured on the Ge QD/Si 3 N 4 structures [ 53 ], and estimated number of interface traps for a 10 nm Ge QDs/Si 3 N 4 structure is approximate unity.…”
Section: Discussionmentioning
confidence: 99%